Psychometric Evaluation and Norms for the Multidimensional Assessment of Interoceptive Awareness (MAIA) in a Clinical Eating Disorders Sample. (17th July 2017) - Brown, Tiffany A.; Berner, Laura A.; Jones, Michelle D.; Reilly, Erin E.; Cusack, Anne; Anderson, Leslie K.; Kaye, Walter H.; Wierenga, Christina E.
Abstract: Altered interoceptive awareness (IA) has been implicated in the pathophysiology of eating disorders; however, few comprehensive self‐report measures of IA exist in eating disorders. The present study sought to validate the Multidimensional Assessment of Interoceptive Awareness (MAIA), originally developed to assess IA in individuals practicing mind–body therapies, in an eating disorder sample. Adult and adolescent patients ( n  = 376) completed assessments upon admission to a partial hospital programme. Analyses examined the factor structure of the MAIA, scale means, scale–scale correlations, internal consistency and construct validity. Analyses also examined associations between MAIA subscales and eating disorder symptoms. Results supported the original eight‐factor structure of the MAIA. Internal consistency was acceptable, and the scales converged with associated measures. Importantly, Not Distracting, Self‐regulation, Body Listening and Trusting were most strongly associated with eating disorder symptoms. Results support use of the MAIA among eating disorders and provide further support for the relevance of IA in eating disorders. Copyright © 2017 John Wiley & Sons, Ltd and Eating Disorders Association.